Implementasi Permainan Tradisional Engklek Dalam Pembelajaran IPA Materi Tata Surya Pada Siswa Kelas VI Sekolah Dasar - Lestari, Dwi; Dia Indah Sari, Arissona (ALENA : Journal of Elementary Education, 2024)
Education at Primary level aims to provide students with a solid foundation of knowledge and help them develop the necessary skills. At this level, creative and fun learning can play an important role in increasing students' understanding and interest in the subject matter. One way to achieve this goal is to implement the traditional engklek game into science learning about the Solar System. The research methodology used is a qualitative descriptive method. The research results show that students are very interested in participating in the traditional engklek game used in science learning. They also succeeded in finding answers to questions and working together with the team to answer them. Thus, the application of the traditional engklek game as a science learning tool in elementary schools is considered effective.